A hybrid GIS and knowledge-driven approach for water resources potential zonation - Umar Saifuddin, Muhammad Firdaus; Ash’aari, Zulfa Hanan; Aris, Ahmad Zaharin; Mohd Kusin, Faradiella (GEOMATE International Society, 2021)
Assessing the potential zone of groundwater is extremely important in areas that are prone to climate-related hazards and have limited access to potable water supply such as Kuala Krai, Kelantan, Malaysia. The application of GIS and remote sensing allows for faster, cheaper, and more efficient groundwater management and exploration. In this work GIS and Knowledge-Driven approach are combined in an attempt to identify groundwater potential zones in Kuala Krai. The various thematic maps prepared for delineating groundwater potential zones are lineament, lithology, soil, land use, rainfall, slope, drainage density, and elevation. The knowledge-driven technique is used to assign weights for each factor and Weighted Linear Combination (WLC) approach is used to investigate several choice possibilities and evaluate suitability according to the associated weight of each factor. The results revealed that 31.64% and 15.10% of the area in Kuala Krai were categorized as high and very high groundwater potential zones which are mostly located in the central, western, and southern parts of Kuala Krai where inter bedded sandstone, siltstone, and shale were the major geological unit. Furthermore, rainfall was also highly influential in determining groundwater potentiality. In terms of land use, forest, rubber, and oil palm were found to be suitable for high potential zones of groundwater. Moreover, the area located nearby the Kelantan River also exhibited high groundwater potentiality. The map can be used to develop and further expand groundwater utilization in Malaysia.